WT1 mutations in T-ALL. - Tosello, V; Mansour, MR; Barnes, K; Paganin, M; Sulis, M; Jenkinson, S; Allen, C; Gale, R; Linch, D; Palomero, T; Real, P; Murty, V; et al. (2009)
The molecular mechanisms involved in disease progression and relapse in T-cell acute lymphoblastic leukemia (T-ALL) are poorly understood. We used single nucleotide polymorphism array analysis to analyze paired diagnostic and relapsed T-ALL samples to identify recurrent genetic alterations in T-ALL. This analysis showed that diagnosis and relapsed cases have common genetic alterations, but also that relapsed samples frequently lose chromosomal markers present at diagnosis, suggesting that relapsed T-ALL emerges from an ancestral clone different from the major leukemic population at diagnosis. In addition, we identified deletions and associated mutations in the WT1 tumor suppressor gene in 2 of 9 samples. Subsequent analysis showed WT1 mutations in 28 of 211 (13.2%) of pediatric and 10 of 85 (11.7%) of adult T-ALL cases. WT1 mutations present in T-ALL are predominantly heterozygous frameshift mutations resulting in truncation of the C-terminal zinc finger domains of this transcription factor. WT1 mutations are most prominently found in T-ALL cases with aberrant rearrangements of the oncogenic TLX1, TLX3, and HOXA transcription factor oncogenes. Survival analysis demonstrated that WT1 mutations do not confer adverse prognosis in pediatric and adult T-ALL. Overall, these results identify the presence of WT1 mutations as a recurrent genetic alteration in T-ALL.